Origin and Emplacement of Acadian Granitic Rocks, Northern Cape Breton Island - Wiebe, Robert A. (Canadian Journal of Earth Sciences, 1975)
Acadian granitic rocks in northern Cape Breton Island consist entirely of even-grained leucocratic granodiorite and adamellite. The compositional range is small, and the average composition corresponds well with melts that could be generated in the crust. Abundant pegmatites in the contact zone suggest high water content.Within the major plutons these granitic rocks show: (1) high scatter on a Rb–Sr isochron (Cormier 1972), (2) apparently random areal variation in K and Ca, but a systematic areal variation in K/Rb and Ca/Sr, and (3) high scatter of Na 2 O and K 2 O on plots against differentiation index. The minor compositional heterogeneity indicated by these relations could have originated within the source region of melting or by assimilation during emplacement.The granitic plutons are elongate north–south and occur in an en echelon pattern within a NNE-trending migmatite zone. The spatial arrangement of pre-emplacement structures in the country rock and the distribution of xenoliths in the intrusions suggest that emplacement was accommodated by east–west expansion, upbowing of the surrounding country rock, faulting, and minor stoping.